Opinion 2432: Scarabaeus ferrugineus Palisot de Beauvois, 1809 (currently Bradycinetulus ferrugineus) (Insecta, Coleoptera, Scarabaeoidea): specific name conserved - ICZN (Bulletin of Zoological Nomenclature, 2019)
The International Commission on Zoological Nomenclature has conserved the usage of the specific names of Scarabaeus ferrugineus Olivier, 1789 (currently Metacatharsius ferrugineus) (Scarabaeidae) and Scarabaeus ferrugineus Palisot de Beauvois, 1809 (currently Bradycinetulus ferrugineus) (Geotrupidae) by ruling that the latter nominal species is not invalid by reason of being a junior homonym of the former.
Keywords: Nomenclature; taxonomy; Scarabaeidae; Geotrupidae; Metacatharsius ferrugineus; Bradycinetulus ferrugineus; Scarabaeus ferrugineus; dung beetles; scarabs